PBL WRAP UP SESSIONS: AN APPROACH TO ENHANCE GENERIC SKILLS IN MEDICAL STUDENTS - Razzaq, Zubia; Ahsin, Sadia (Journal of Ayub Medical College Abbottabad, 2011)
Background: Problem based learning (PBL) tutorials are being used in various medical schools world wide. Students’ active participation is a must for the success of a teaching program. The objective of this study was to evaluate the effectiveness of PBL Wrap-up sessions in an integrated modular medical curriculum in enhancing the generic skills of medical students. Methodology: This study was conducted on 100 students of 2nd year MBBS who had been taking PBL sessions since 1½ years. Each session concluded with a wrap-up session where students demonstrated their acquired knowledge in the form of PowerPoint presentations, concept maps, skits, models etc. A questionnaire based survey was conducted to find out overall effectiveness of PBL sessions including wrap-up sessions. The questionnaire comprised of 15 questions. Students were asked to rate all those sessions on a likert scale of 1 to 5. Results: Student’s responses showed ’˜Moderate improvement’ in 8 out of 15 skills like communication with peers and teachers, presentation skills, self confidence, application of acquired knowledge, using internet and other resources and understanding group dynamics. Improvement in abilities like problem solving, time management, creativity, motivation in studies and self-directed learning was ’˜Minimal’. In addition students recommended continuation of PBL in the same way for future classes. Conclusion: PBL with wrap-up sessions contributed in bringing moderate enhancement of generic learning skills in students which were not properly addressed in the traditional curriculum and are therefore recommended for future implementation. Keywords: PBL, learning skills, teaching techniques, Student-centred Classroom,